Hydrolysis of neostigmine by plasma cholinesterase - Nowell, P. T. (1962)
Incubation of neostigmine with normal human plasma in vitro results in the formation of two quaternary nitrogen compounds, one of which has been identified as m-hydroxyphenyltrimethylammonium. This hydrolysis is prevented by prior addition of dyflos to plasma in concentrations sufficient to inhibit plasma cholinesterase activity. The significance of these findings is discussed in relation to the occurrence of the same metabolic products in the urine of patients with myasthenia gravis treated with oral neostigmine. No equivalent findings are available for normal subjects since it was not considered justifiable to treat them with neostigmine.